PRINCIPAL STRATEGY FOR OPTIMIZING SCHOOL-BASED MANAGEMENT IN A FOUNDATION-RUN HIGH SCHOOL - Rivaldo Paul Telussa; Neti Bunai; Maria Ria Butu; Nazar Amrullah; Suardiman Dayadi; Aleks Pigai (CV. TOTUS TUUS, 2026)
School-based management (SBM) requires school-level autonomy to be supported by participation, accountability, role clarity, and the capacity to use limited resources. This qualitative single-case study examines how a principal described and enacted SBM in a foundation-run high school in Nabire, Papua. The principal was the sole primary informant. The available research record indicates that data were collected through an in-depth interview, observation, and document review, although the fieldwork period and detailed collection procedures were not documented. A framework-guided thematic analysis organized the account around planning, resource organization, program implementation, monitoring and evaluation, enabling and constraining conditions, and proposed responses. The principal reported an annual work program, formal task allocation, supervision and teacher-development activities, and periodic evaluation meetings. Implementation was constrained by uneven participation, limited resources, overlapping duties, weak program indicators, and uneven understanding of SBM. Because the research record did not include verbatim quotations or traceable observation and document identifiers, the findings are interpreted as a descriptive managerial account rather than verified evidence of school-wide effectiveness. The study proposes that formal routines become more participatory and learning-oriented when shared understanding, decision rights, role clarity, measurable indicators, and foundation-school accountability are aligned. The findings are analytically transferable to comparable settings but are not statistically generalizable.